1987
DOI: 10.1111/j.1471-0528.1987.tb02257.x
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde ejaculation: a systematic approach to non‐invasive recovery of spermatozoa from post‐ejaculatory urine for artificial insemination

Abstract: Retrograde ejaculation is an uncommon but treatable form of male infertility. Successful recovery of live spermatozoa from the post-ejaculatory urine for artificial insemination is dependent on careful regulation of pII and osmolarity of the urine into which ejaculation takes place, and separation of the motile spermatozoa from the debris and cells which are found in these samples. Three pregnancies established by artificial insemination o f spermatozoa recovered by noninvasive means from the bladders of men s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Motile spermatozoa were not found in urine specimens with a pH < 5.5 ( Makler et al ., 1981 ; Zavos & Wilson, 1984). A pH > 9.0 is spermatotoxic ( Braude et al ., 1987 ). It has been reported that sperm motility is maintained over a very large range of osmolality (200–800 mOsm/kg) with better survival under hypertonic rather than hypotonic conditions ( Makler et al ., 1981 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Motile spermatozoa were not found in urine specimens with a pH < 5.5 ( Makler et al ., 1981 ; Zavos & Wilson, 1984). A pH > 9.0 is spermatotoxic ( Braude et al ., 1987 ). It has been reported that sperm motility is maintained over a very large range of osmolality (200–800 mOsm/kg) with better survival under hypertonic rather than hypotonic conditions ( Makler et al ., 1981 ).…”
Section: Discussionmentioning
confidence: 99%
“…(1995 ) reported that urine, even at a low concentration, was deleterious to sperm function and that this effect might involve other biochemical factors that are unrelated to urine pH and osmolality. Contamination of the semen with cells and debris ( Braude et al ., 1987 ) and bacteria ( Auroux et al ., 1991 ) found in urine can also have detrimental effects on sperm motility ( Braude et al ., 1987 ; Auroux et al ., 1991 ). In this regard, the biochemical compounds present in urine cannot be ignored; however, their effect on sperm motility has attracted little attention so far ( Crich & Jequier, 1978; Ronquist et al ., 1985 ).…”
Section: Introductionmentioning
confidence: 99%
“…Both, high urine osmolality and low pH are considered toxic to spermatozoa, and hence, both parameters need optimization to enhance sperm survival [ 5 27 28 29 ]. Urine preparation in the patients with RE can be performed by ingestion of oral alkalinizing agents [ 29 ].…”
Section: Optimization Of Urine Ph and Osmolality For Improved Sperm V...mentioning
confidence: 99%
“…We altered the dosage to just twice-5 gm each at 2 h and 1 h prior to ejaculation-and found a consistent pH between 7.3 to 7.6. Similarly, Braude et al [4] were able to maintain the pH between 7.6 and 8.1 by giving one dose of 5-10 gm NaHCO, 2 to 3 h before voiding for spermatozoa collection. Perhaps the slightly higher pH reported by Braude et al…”
Section: Sperm Preparationmentioning
confidence: 99%